SLEEP QUALITY AND DEMAND FOR SLEEP-ENHANCING TRADITIONAL MEDICINE AMONG VIETNAMESE TRADITIONAL MEDICINE STUDENTS OF A MEDICAL UNIVERSITY: A CROSS SECTIONAL STUDY (Vietnam Journal of Community Medicine, 2026)
Objective: Poor sleep quality is highly prevalent among medical students and adversely affects health and academic performance. The study aimed to describe prevalence of poor sleep quality (Pittsburgh Sleep Quality Index (PSQI)>5), to characterize sleep hygiene and PSQI subcomponents, and secondarily to examine the association between sleep hygiene as measured by the Sleep Hygiene Index (SHI) and poor sleep as well as to determine the demand for traditional medicine methods to improve sleep among Traditional Medicine students at medical university.Methods: The study was a cross‑sectional survey of 517 students (stratified and convenience sampling). PSQI and SHI were used to measure sleep quality and sleep hygiene. Primary analyses were descriptive (prevalence, means, proportions); secondary/exploratory analyses examined associations using Chi-square test (α = 0.05).  Results: 50.7% had poor sleep quality (PSQI>5 - a subjective screening threshold at the time of the survey, rather than a clinical diagnosis of a sleep disorder); 59.6% expressed demand for traditional medicine (most preferred: acupressure massage 31%). In secondary analyses, poor sleep hygiene was significantly associated with poor sleep (PR=1.63; 95% CI 1.27-2.09; p
Keywords: sleep quality, sleep hygiene, traditional medicine methods, PSQI.